Science Communicators on TikTok: Content Strategies in the Digital Age - Micaletto Belda, Juan Pablo (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
This research analyzes the methods and content strategies employed by science communicators on TikTok. The aim is to understand these dynamics and identify aspects of the platform that facilitate science communication. Through an online survey, it is observed that late afternoon and evening hours are suitable for posting science-related videos. A humorous and informative tone should stand out in these productions. Additionally, it is necessary for these prosumers to be familiar with aspects such as the algorithm, hashtags, visual effects, or current trends to effectively discuss science.